Cellular senescence of renal tubular epithelial cells in renal fibrosis - Zhang, Jun-Qing; Li, Ying-Ying; Zhang, Xue-Yan; Tian, Zeng-Hui; Liu, Cheng; Wang, Shi-Tao; Zhang, Fa-Rong (Frontiers in Endocrinology, 2023)
Renal fibrosis (RF) is the common pathological manifestation of virtually all chronic kidney diseases (CKD) and one of the major causes of end-stage renal disease (ESRD), but the pathogenesis of which is still unclear. Renal tubulointerstitial lesions have been identified as a key pathological hallmark of RF pathology. Renal tubular epithelial cells are the resident cells of the tubulointerstitium and play an important role in kidney recovery versus renal fibrosis following injury. Studies in recent years have shown that senescence of renal tubular epithelial cells can accelerate the progression of renal fibrosis . Oxidative stress(OS), telomere attrition and DNA damage are the major causes of renal tubular epithelial cell senescence. Current interventions and therapeutic strategies for cellular senescence include calorie restriction and routine exercise, Klotho, senolytics, senostatics, and other related drugs. This paper provides an overview of the mechanisms and the key signaling pathways including Wnt/β-catenin /RAS, Nrf2/ARE and STAT-3/ NF-κB pathway involved in renal tubular epithelial cell senescence in RF and therapies targeting renal tubular epithelial cell senescence future therapeutic potential for RF patients. These findings may offer promise for the further treatment of RF and CKD.